Effect of coastal front and water masses on the spatial pattern of sedimentary biomarkers in the East China Sea - Liu, Zili; Jia, Yonghao; Fang, Yin; Wang, Yujue; Gao, Jianhua; Duan, Yunying; Li, Meng; Wang, Qi; Liu, Dongyan (Continental shelf research, 2025)
Coastal fronts are important physical boundary between coastal and offshore water masses in the ocean. The secondary circulation generated by fronts can greatly impact matter transport across fronts, leading to the different sedimentary environments between water masses. To understand the combined effects of fronts and water masses on the sedimentary environment in the East China Sea, we studied the spatial patterns of grain size, organic matter and biomarkers in surface sediments crossing the Min-Zhe Coastal Front (MZCF), combined with observational data in the upper ocean. The results showed that the front and water masses jointly determined the spatial pattern of sedimentary environments in the East China Sea. Marine organic matter dominated in the mud area, with higher concentrations at the frontal region. Terrestrial organic matter exhibited a decreasing trend from nearshore to offshore, particularly at the frontal shore-side, indicating the barrier effect of the front on coastal matter transport. The mean ratio between brassicasterol and dinosterol (B/D) in the sediments of MZCF and East China Sea coastal water mass (ECSCoW) was 2.8, which was lower than the B/D (3.8) in the sediments of East China Sea shelf water mass (ECSSW) and indicated that dinoflagellates are confined at the frontal shore-side water mass. The spatial patterns of diatom and dinoflagellate pigments in the water column were consistent with the biomarker patterns in the sediments and corresponded to the different habitats (e.g., nutrients, salinity) generated by the ECSCoW, ECSSW, and MZCF. The study explained the combined effects of front and water masses on sedimentary environments in the East China Sea and suggested to use fronts as boundary to distinguish water mass environments in paleo-oceanographic reconstruction. •The marine organic carbon show high values in the frontal zone and nearshore areas.•The relative contributions of diatoms and dinoflagellates vary across water masses.•Fronts and water masses determined the spatial patterns of sedimentary environment.